Nilai-Nilai Pendidikan Islam Dalam Sejarah Dakwah Nabi Muhammad di Madinah Sebagai Sarana Penanaman Karakter Pada Remaja - Nurdianzah, Erry; Mahbub Wijaya, Mirza (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2023)
This research aims to examine and analyze the success of the Prophet Muhammad SAW's preaching in Medina, so that this success includes the character values taught by the Prophet Muhammad SAW as the main role model for Muslims. This research is qualitative literature research with a historical approach. So data collection was carried out by examining historical texts through books, journals and other documents relevant to the study topic, and then presented descriptively.  Data collection was carried out by examining historical texts through books, journals and other documents relevant to the study topic, and then presented descriptively. The results of this research show that the success of the Prophet Muhammad's preaching in Medina cannot be separated from the prophet's humanist behavior, obedience to Allah SWT, ukhuwah, peace and unity. Meanwhile, in cultivating these character values, mentoring, stories and example methods can be used.